(untitled) (Journal of the College of Basic Education, 2025)
The study aimed to find out the effect of using the polya model on the mathematical coherence skills of fourth grade students in mathematics. The quasi-experimental design was chosen، and the study sample consisted of 77 students distributed into two groups: the experimental (39) students and the control (38) students، and after conducting the equivalence process between the two groups. In some variables that are believed to affect the conduct of the experiment، the experimental group studied according to the steps of the (polya) model and the second (control) group studied according to the usual method. The two groups studied in the three chapters (basic concepts in geometry and vectors، basic concepts in coordinate geometry، Statistics) for the content of the mathematics book for the fourth scientific grade، after completing the teaching process، the two groups applied the study tool، the Mathematical Interconnection Skills Test، which consists of (20) items. Appropriate statistical methods were used to analyze the results، and the statistical analysis program SPSS was used. The results of the study indicated that there was a statistically significant positive effect of the model on mathematical interconnection skills compared to the usual way.